2020
DOI: 10.3389/fmicb.2020.566473
|View full text |Cite
|
Sign up to set email alerts
|

Screening, Safety Evaluation, and Mechanism of Two Lactobacillus fermentum Strains in Reducing the Translocation of Staphylococcus aureus in the Caco-2 Monolayer Model

Abstract: Staphylococcus aureus is a common commensal of humans, and its translocation from gastrointestine to peripheral organs and tissues could cause severe diseases and complications. This study focuses on the screening and characterization of Lactobacillus strains with significant inhibitory effect on the translocation of S. aureus through Caco-2 monolayers. First, strains with strong affinity for mucin and Caco-2 cells were obtained, via microtiter plate assay and adhesion assay, respectively. Obtained bacteria we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…An animal study showed that L. plantarum ZLP001 pretreatment alleviated the reduction in junction proteins (claudin-1, occludin, and ZO-1) ( 61 ), which are the key contributors to establishing an effective intestinal barrier ( 62 ). Several in vitro experiments also showed that lactobacilli positively affect gut permeability, as incubation of Caco-2 cells with different Lactobacillus strains was found to restore impaired intestinal barrier ( 63 , 64 ).…”
Section: Lactobacillus Inhibits Pathogenic Bacteria and Reduces Gut Permeabilitymentioning
confidence: 98%
“…An animal study showed that L. plantarum ZLP001 pretreatment alleviated the reduction in junction proteins (claudin-1, occludin, and ZO-1) ( 61 ), which are the key contributors to establishing an effective intestinal barrier ( 62 ). Several in vitro experiments also showed that lactobacilli positively affect gut permeability, as incubation of Caco-2 cells with different Lactobacillus strains was found to restore impaired intestinal barrier ( 63 , 64 ).…”
Section: Lactobacillus Inhibits Pathogenic Bacteria and Reduces Gut Permeabilitymentioning
confidence: 98%
“…Moreover, it was also evaluated as antimicrobial agent against infections caused by Candida spp. [ 12 , 18 ], Salmonella typhimurium [55] and Staphylococcus aureus [47] . Therefore, the industrial production of L. fermentum -based probiotic products is of great interest.…”
Section: Introductionmentioning
confidence: 99%